Adsorption of pharmaceutical and heavy metal contaminants onto three-dimensional graphene based structures - Hiew, Billie Yan Zhang (2020)
Water contamination by pharmaceutical and heavy metal discharge is a serious environmental issue causing adverse effects on aquatic biota and human health. Despite showing promising pollutants decontamination efficiency, graphene oxide (GO) nanosheets are not feasible adsorbents for application in wastewater treatment. Therefore, three-dimensional (3D) graphene structures were synthesised and demonstrated to be practical adsorbents for pharmaceutical and heavy metal pollutants removal. This thesis describes the successful conversion of GO nanosheets into graphene macrostructures for the adsorption of pharmaceuticals and heavy metals from aqueous environment.